Pengembangan Flipped Classroom Untuk Mata Kuliah Belajar Berbasis Komputer di Universitas Negeri Jakarta - ZARA LARASATI; Kunto Imbar Nursetyo; Cecep Kustandi (Universitas Negeri Jakarta, 2019)
This development research aims to produce flipped classroom learning in universities generally, especially to computer-based learning courses. Products development included lecture syllabus, guide and course site. The objectives of this study were computer-based study lecturers and first year of educational technology students. This research development is used as a rapid prototype development model that has five stages, namely, assess needs & analyze content, set objectives, construct prototype, utilize prototype, install and maintain system. The evaluation in this study was carried out through expert reviews, namely learning design experts, material experts, and media experts. The average value obtained form learning design expert is 3.7. The average value obtained from material experts is 3.8. The average value obtained form of media experts is 3.3. Through the three evaluations that have been carried out, it can be summarized that the development of flipped classroom learning for computer-based learning courses has been very good and can be utilized by lecturers.